ANALISIS KEMENANGAN H. SUPRIYADI,S.Sos TERPILIH YANG KEDUA KALINYA SEBAGAI CALON ANGGOTA DPRD KOTA SEMARANG 2014 – 2019 DILIHAT DARI PRESPECTIVE POLITIK - Himawan, Cholil Joko; Utomo, Susilo; Astuti, Puji (Journal of Politic and Government Studies, 2016)
H. Supriyadi S.Sos is a PDIP legislators elected a second time, he was also a member of the legislative background of Private and obtain a second vote. Obtaining statistical data acquisition H. Supriyadi S.Sos voice, demonstrated the superiority and the advantages and performed as well as the implementation of the other defeated candidates not elected in the legislative elections contestants Dapil II Semarang form political strategies chosen. Political strategies is an imaging strategy Parties conducted by H. Supriyadi S.Sos, in approaching the community to achieve the goal of winning the legislative elections to gain the sympathy of the public. Formulation of the problem Seen from the point of political strategy, why H. Supriyadi. S.Sos chosen a second time as a member of Parliament Semarang.Descriptive method is a kind of research relating to the collection of data to provide a snapshot of a social phenomenon or state of the subject or the object of the research is based on facts which appear as the descriptive is a type of research relating to the collection of data to provide a snapshot of a social phenomenon or state of the subject or the object of research.The encouraging results of research and background H. Supriyadi.S.Sos become Chairman of the regional council of Semarang that encourages and background became Chairman of the Parliament is that I started my political career in the Indonesian Democratic Party of Struggle (PDIP) as a grass-roots cadres. As a member, at the lowest levels. Being a member of the party, its existence is quite prominent that friends supported his fellow members to occupy the Chair of Children's Village Branch VIII PDI Bulu Lor (1997-2000).Keywords: Victory Strategies H. Supriyadi, S.Sos using SWOT.